Annual cellulose crop options for ethanol and oil cropping intensification for biodiesel feedstocks - Ballard, Todd Curtis (Kansas State University, 2012)
Ethanol from cellulose and biodiesel are both advanced biofuels according to the renewable fuel standard version two (RFS2) as part of the Energy Independence and Security Act of 2007. Agricultural production of feedstocks for these fuels can occur as co-products from the primary use of the crops. Use of cellulosic material produced from annual grain and sugar crops does not displace land use from grain and sugar production. Production of corn (Zea mays L.), grain sorghum, dual purpose forage sorghum, sweet sorghum, and photoperiod sensitive sorghum (Sorghum bicolor (L.) Moench) are all primarily driven for products other than cellulosic ethanol. Corn production if driven by grain and silage markets with fodder occasionally used for forage. Grain sorghum production is driven by grain markets and grown primarily in semi arid regions. Dual purpose forage sorghum is used for forage both as baled hay and as silage. Sweet sorghum is produced for sugar and molasses production. Photoperiod sensitive sorghum is produced for baled hay. The current study tests the effect of seeding rate on cellulosic ethanol on each crop. Yellow grease is the most common source of oil for biodiesel production. Intensification of oil crop production may increase the feedstock availability for biodiesel. The current study uses double cropping of spring camelina (Camelina sativa (L.) Crantz), spring canola (Brassica napus L.), sesame (Sesamum indicum L.), safflower (Carthamus tinctorius Mohler, Roth, Schmidt and Bourdeux), soybean (Glycine max L.), and sunflower (Helianthus annuus L.) to search for cropping system options that will produce more oil on an annual basis than full season crops. The full season crop options used were maturity group IV soybean, maturity group V soybean, and full season sunflower. Fertility inputs are inherently less for the non legume crops due to the N fixation ability of symbiotic rhizobium. Canola and camelina are also more sensitive to sulfur deficiency than many crops. Long chain and polyunsaturated fatty acids have higher market values than biodiesel. Separation of these fatty acids from the lipid profile of oil seed crops provides additional demand for oil seed crops. Demand for the crops will drive commodity prices and move land use into oil crop production. The second year of oilseed production provided an opportunity to look at lipid profiles of successfully produced crops during a drought year. Three new discoveries were concluded. Grams cellulosic ethanol g[superscript]-1 stover is not affected by density within the densities considered. Among the double crop options tested only sesame after spring crops was viable in normal years and none were viable in an extreme drought year. Lipid profiles are provided for crops produced in concurrent field growing conditions.
Keywords: Agronomy; Biofuels; Ethanol; Biodiesel; Agronomy (0285); Alternative Energy (0363)